Effect of hydrogen supplementation on engine performance and emissions. (12th April 2018) - Sharma, Priybrat; Dhar, Atul
Abstract: Vehicular Pollution and environmental degradation are on the rise with increasing vehicles and to stop this strict regulation have been put on vehicular emissions. Also, the depleting fossil fuels are of great concern for energy security. This has motivated the researchers to invest considerable resources in finding cleaner burning, sustainable and renewable fuels. However renewable fuels independently are not sufficient to deal with the problem at hand due to supply constraints. Hence, advanced combustion technologies such as homogeneous charge compression ignition (HCCI), low-temperature combustion (LTC), and dual fuel engines are extensively researched upon. In this context, this work investigates dual fuel mode combustion using a constant speed diesel engine, operated using hydrogen and diesel. The engine is operated at 25, 50 and 75% loads and substitution of diesel energy with hydrogen energy is done as 0, 5, 10 and 20%. The effect of hydrogen energy share (HES) enhancement on engine performance and emissions is investigated. In the tested range, slightly detrimental effect of HES on brake thermal efficiency (BTE) and brake specific fuel consumption (BSFC) is observed. Comparision of NO and NO2 emissions is done to understand the non-thermal influence of H2 on the NOx emissions. Hence, HES is found beneficial in reducing harmful emissions at low and mid loads. Highlights: Timed manifold hydrogen gas injection. Effect of hydrogen energy share enhancement on engine performance and emissions. NO and NO2 emissions. Particulate number and size distribution under hydrogen diesel dual fuel combustion.